Proporsi Ibu Hamil Risiko Tinggi yang Dirujuk pada Daerah Tertinggal - M. Lukman Arsyad (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: This study was carried out to know scope primary health care especially for proportion of pregnant with high risk which were reference service. After five years be in effect decentralization include health department, this study was from July to September 2006 in under develop areas as location of study.Method: The study design using secondary data by “data extraction” or observation study with “survey method” and data processing using by Microsoft Excel for Windows and descriptive statistical analysis. This study will be measure for proportion of pregnant with high risk which were reference service in under develops area.Result: This study will be preparation health information about proportion of pregnant with high risk which reference services in were under develop areaConclusion: The means of under develop area were not the target of indicators minimal health service standard yet reached.Keywords: pregnant with high risk reference